Changes of the linear energy transfer (LET) and beam width of therapeutic carbon ion beam in density heterogeneous phantoms. (1st June 2022) - Yang, Shiyan; Zhao, Jingfang; Zhuo, Weihai; Shen, Hao; Chen, Bo
Abstract: This work aims to investigate the changes in the linear energy transfer (LET) spectra distribution and the beam spot width of a therapeutic carbon ion beam in density heterogeneous phantoms. Three different heterogeneous phantoms were fabricated using a combination of solid water, lung, and bone tissue slabs and irradiated by a single energy carbon beam (276.5 MeV u −1 ). CR-39 detectors were used for experimental measurements and the Monte Carlo toolkit Geant4 was employed for theoretical simulations. The results demonstrated that the measured LET spectra agree well with the simulation results. The lung and bone tissues displayed no obvious effect on the spectral distribution of LET. The dose-average LET was invariant and showed no obvious difference in the different materials, while the track-average LET increased in the lung and decreased in the bone materials. Similarly, the beam spot size increased in the lung, and decreased in the bone materials. Additionally, the fluence of the secondary fragments varied in different tissues. These findings are expected to provide cross-validation data for the quality assurance of carbon ion therapy and to be beneficial for validating the base data in treatment planning systems.